Paragenesis and geochemistry of the Miocene Milestone sinter, Silver City District, ID: implications for sinter-hosted epithermal Au-Ag deposits - Fenner, Emily Ruth (Kansas State University, 2020)
The Milestone sinter is a mid-Miocene epithermal paleosurface that is spatially associated with the DeLamar silver-gold deposit in the Silver City District, Idaho. The exact connection between Milestone and DeLamar, along with other deposits across the northern Great Basin, remains unknown. Additionally, the economic potential of Milestone has not been evaluated since Barrett (1985), where it was found to host Au and Ag. Geologic mapping of the Main Knob of Milestone reveals five lithofacies in the paleosurface: Matrix-supported breccia, clast-supported breccia, sinter, geyserite, and bioformations. The facies are indicative of a paleohotspring, typical of modern hot spring environments. Reflective light imagery and traditional microscopy show multiple quartz textures, electrum microparticles, pyrite relicts, and pyragyrite crystals. LA-ICP-MS data of trace elements show up to 2.84 wt % Ag and 153 ppm Au in sinter samples. The occurrence of precious metals in the sinter may be indicative of metal-rich veins at depth. Across the flow path from vent to distal apron, there is no relationship between precious metal deposition and flow path location (i.e. temperature variations). The fluids of the epithermal system took advantage of the faults and other structural weaknesses in the Silver City District much modern systems in Yellowstone National Park and the Taupo Volcanic Zone. The underlying Silver City rhyolite has an age of about 16.1 Ma (Brueseke and Hames, unpublished), and the mineralized veins in other Silver City District locations (e.g. War Eagle Mountain, Florida Mountain) have ages of ~15.5 to 15.8 Ma (Aseto, 2012; Mason et al., 2015). It is likely that Milestone formed in the same ~15.5 to 15.8 Ma age time interval.
Keywords: Geology; Hot Spring; Epithermal Deposits; Sinter; Hydrothermal Deposits; Economic Geology